Daily timescale dynamics of planktonic foraminifera shell-size distributions - Chernihovsky, Natalie; Torfstein, Adi; Almogi-Labin, Ahuva (Frontiers in Marine Science, 2023)
Planktonic foraminifera (PF) shells comprise a significant fraction of the global oceanic carbonate flux and serve as a primary archive of the history of the oceans. Yet, a limited understanding of their life cycles dynamics and biological rhythms, hampers their application as palaeoceanographic proxies. Here, we present the flux of ten PF species and their shell-size distributions at a daily timescale resolution in the Gulf of Aqaba (GOA), northern Red Sea. We report diameter measurements of ~13,500 shells, associated with ten PF species, retrieved using an automated time-series sediment trap deployed at a water depth of ~410 m (seafloor depth 610 m) throughout more than a full annual cycle between 2015 and 2016. Most of the PF species display a wide intraspecific shell-size distribution among adult PF, while six abundant species (G. ruber, G. rubescens + G. tenellus, G. glutinata, G. calida and G. siphonifera) display significantly smaller shell-sizes compared with corresponding specimens from sediment traps and seafloor sediments across other tropical, subtropical and upwelling regions. The results indicate that PF generation cycles can be classified according to three patterns: (1) Quiescent: minimal shell-size and extended life cycles due to unfavorable conditions and food scarcity when the water column is stratified and oligotrophic, (2) Transient: the gradual increase of Chlorophyll-a (Chl-a) concentrations and food availability enhance shorter life-cycles, although PF do not necessarily reach maximal shell-sizes, (3) Successive: PF fluxes and Chl-a concentrations are maximal, the generation time is extended and individuals might display growth to maximal shell-sizes.